Exploring the Synthesis of Human Milk Oligosaccharides and Their Effects on Immunometabolism - Slater, Alanna (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2026)
Human milk oligosaccharides (HMOs) are the third most abundant component of human milk after lactose and lipids, yet were long considered to play only a passive, gut-localised nutritional role. In that context, they were largely characterised as prebiotic substrates, selectively fermented by commensal microbes to generate immunomodulatory short-chain fatty acids. However, HMOs are not simply dietary components confined to the intestinal lumen. Their synthesis is the result of tightly regulated activity by a family of glycosyltransferase enzymes expressed within mammary epithelial cells (MECs), which dictate the structural diversity and functional specificity of these glycans. Importantly, evidence now confirms that a proportion of ingested HMOs can translocate across the intestinal barrier and enter systemic circulation, implying that their biological activity extends beyond the gut-microbiota axis and may involve direct engagement with circulating immune cells. This thesis explores their role as active immunometabolic signals that directly influence cellular energetics and effector function across innate immune lineages. Through the use of highly purified 2'-fucosyllactose (2'-FL), 3'-sialyllactose (3'-SL), and 6'-sialyllactose (6'-SL), Chapters 3-5 interrogate macrophages, dendritic cells (DCs), and T-cells across basal and inflammatory states. Metabolic flux analysis, transcriptional profiling, complex assays, ROS and cytokine measurements, phagocytosis assays, and receptor signalling readouts collectively demonstrate that HMOs do not act as uniform anti- or pro-inflammatory agents. Instead, they function in a structure and context dependent manner; sialylated HMOs suppress mitochondrial respiration while enhancing glycolysis, priming macrophages for antimicrobial readiness yet preventing hyperinflammation, whereas 2'-FL preserves oxidative balance and restrains activation. In DCs, 6'-SL in particular, enforces metabolic quiescence, while T-cells remain largely unaffected; supporting a model in which adaptive immunity is shaped indirectly through antigen-presenting cells rather than direct glycan interference. These findings establish HMOs as context-sensitive immunomodulators that reprogramme immune cell metabolism to shape downstream function, aligning them with the broader paradigm of immunometabolism. Structural variation may correlate with immunological potency, but most HMOs, remain prohibitively expensive or unavailable due to limitations in microbial, enzymatic and chemical synthesis platforms. Chapter 6 confronts this bottleneck by attempting to reconstruct HMO biosynthesis within mammalian cells. HEK293 cells were engineered with selected glycosyltransferases in an attempt to determine whether endogenous metabolic machinery could be leveraged to generate sialylated oligosaccharides in vitro. Catalytic specificity was retained across constructs, enabling low but detectable production of terminally sialylated HMOs, supported by intracellular nucleotide sugar pools. Crude glycosyltransferase isolation assays further revealed that enzyme activity was pH dependent, with optimal production observed at pH 6.5. Collectively, these findings establish a foundation for scalable cell-based synthesis not only of simple structures such as 3'-SL and 6'-SL, but potentially of more complex branched glycans including lacto-N-neotetraose (LNnT). Together, this data delivers two key messages. First, HMOs are not inert sugars but rather immunometabolic regulators with structure specific signalling capacity. Second, their therapeutic potential remains under explored not because of biological uncertainty, but because of manufacturing constraints. HMOs will require the development of further re-engineered biosynthetic platforms before they can be used clinically. This thesis therefore advances both immunological understanding and translational feasibility, highlighting HMOs as a class of maternally derived immune regulators and identifying the cellular and engineering strategies required to understand their full therapeutic value.
APPROVED
Keywords: Human Milk Oligosaccharide; Macrophage; Immunometabolism; Dendritic Cell; T cell; Glycoengineering